Petrykivka Painting: Political Implications of Cultural Heritage in Ukraine - Voloshyna, Iryna (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
Discussions about the issues of heritage and ownership of culture have become especially heated in the current political climate in Ukraine. In the process of re-writing the Soviet historical narrative and re-claiming their national and cultural identity, it is very important for Ukrainians to mark their geographical and cultural borders. Heritagization plays an extremely important role in this process. In this paper, I use the example of Petrykivka painting as a case study to illustrate the current tendencies and problems with claiming heritage. Deploying the tools of critical heritage studies, I want to explore two themes: 1) how the process of heritagization has been a political act, used both by the Soviets and in independent Ukraine, but with different agendas; and 2) the long-standing effects of such heritagization and involvement of international cultural organizations in it.